VIEWS HUSBAND'S WIFE WORKED IN DESAPETAPAHAN JAYA KECAMATAN TAPUNGKABUPATEN KAMPAR - Halim, Amir; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study entitled “Views on Wife Husband Work in DesaPetapahan Jaya Kecamatan TapungKabupaten Kampar”. This research was conducted in DesaPetapahan Jaya Kecamatan TapungKabupaten Kampar. The purpose of this study was to determine why the wife works full-time in DesaPetapahan Jaya Kecamatan TapungKabupaten Kampar. Topics focus of this research was how the wife of the husband who worked full-time in DesaPetapahan Jaya Kecamatan TapungKabupaten Kampar. Object Research is a married couple who worked as many as five pairs of husband and wife in DesaPetapahan Jaya Kecamatan TapungKabupaten Kampar”. The author uses qualitative descriptive method and the data were analyzed quantitatively and using the technique of taking Puspoive sampling. Instruments Data were observation, interviews and documentation. Research conducted in Desa Petapahan Jaya Kecamatan Tapung Kabupaten Kampar Regarding the views Husband Wife Works produces analysis or research results as follows:Husband and wife assume very negligent in caring for the purposes of her husband and children. The wife often overlook some quality time with her husband and her children because they are busy with routine work that can not be tolerated by the husband, wife thought that the husband becomes just like status in a course of their marriage. Because liabilities, functions and roles of the wife is not working as it should, harshness wife's desire to keep working often led to keretaka relationship between them. Often large families were subjected to the conflict between husband and wife. Keywords: Satisfaction of Household, Wife Works.